The Impact of Low Oil Prices on the Trade Balance of Balkan Countries and their Energy Security - Obadi, Saleh Mothana; Kosir, Igor; Korcek, Matej (Energy Economics Letters, 2017)
This chapter examines the impact of low oil prices in the last years on the trade balance of Balkan countries and their energy security. The development of oil prices in the last years has a potential impact on all economies. Indeed the impact was positive for crude oil importing economies but in the other hand, negative impact on crude oil exporting economies. According to our analysis, the impact was positive on all Balkan economies, regardless the scale of the impact. The positive impact was clear on the trade balance of all Balkan countries, for example in 2015 they registered a significant decrease in their deficit of trade balance comparing to 2011. For the energy security of Balkan should be insured by other alternative energy resources, among them natural gas and renewable energy resources.